Communication Matters: How Do Visitors Interact with Ethnographic Open-Air Museums? - Charapan, Nadzeya (Information & Media, 2018)
[full article, abstract in English; abstract in Lithuanian]Though the concept of an ethnographic open-air museum is not a new one, little is known about the interplay between a visitor and an amalgam museum setting. Ethnographic open-air museums are complex spaces with shared qualities of outdoor sites and indoor museums. Grounded in Gibson’s theory of affordances (1979), the article explores how visitors interact within and in relation to the hybrid space of ethnographic open-air museum and how communication shapes their interactions. The analysis is based on a qualitative study of visitors in the Belarusian State Museum of Folk Architecture and Rural Lifestyle (Aziartso, Belarus) and the Open-Air Museum of Lithuania (Rumšiškės, Lithuania). The data were collected using participatory observation and semistructured interviews with visitors. The article employs a constructivist approach and conceptualizes an ethnographic museum as a free-choice environment, where behavior patterns are linked to the institutional context and the visitors’ ability to perceive the information about the objects and environments that specified the possibilities and constraints for interacting with the museum’s space. The study reveals how cultural communication fosters the diversity of visiting scenarios and the perceptions of ethnographic open-air museums as cultural heritage sites, natural parks and stages for entertainment. The implications of this research could be relevant to cultural policymakers and communication specialists in designing the cultural, recreational and educational policies of museums.
Keywords: affordances; communication; ethnographic open-air museums; information